Editorial - Tsouchlaraki, Georgia-Zoi; Plevridi, Katerina (Conatus - Journal of Philosophy, 2018)
This special issue includes essays that cover a broad spectrum of Aristotle's though. It's purpose is to highlight Aristotle's seminal contribution to philosophy, focusing in particular on his views on politics, ethics, and aesthetics, as well as on his decisive contribution to the sciences, for many of which he is considered to have been the founder, most notably physics and biology. The variety of topics that are discussed in this special issue is indicative of the paramount significance of Aristotle's teaching with regard to various aspects of human intellectual production,